Application of non-linear k-e turbulence model in flow simulation over underwater axisymmetric hull at higher angle of attack - Sakthivel, R; Vengadesan, S; Bhattacharyya, S K (Journal of Naval Architecture and Marine Engineering, 2011)
This paper addresses the Computational Fluid Dynamics Approach (CFD) to simulate the flow over underwater axisymmetric bodies at higher angle of attacks. Three Dimensional (3D) flow simulation is carried out over MAYA Autonomous Underwater Vehicle (AUV) at a Reynolds number (Re) of 2.09×106. These 3D flows are complex due to cross flow interaction with hull which produces nonlinearity in the flow. Cross flow interaction between pressure side and suction side is studied in the presence of angle of attack. For the present study standard k-ε model, non-linear k-ε model models of turbulence are used for solving the Reynolds Averaged Navier-Stokes Equation (RANS). The non-linear k-ε turbulence model is validated against DARPA Suboff axisymmetric hull and its applicability for flow simulation over underwater axisymmetric hull is examined. The non-linear k-ε model performs well in 3D complex turbulent flows with flow separation and flow reattachment. The effect of angle of attack over flow structure, force coefficients and wall related flow variables are discussed in detail. Keywords: Computational Fluid Dynamics (CFD); Autonomous Underwater Vehicle (AUV); Reynolds averaged Navier-Stokes Equation (RANS); non-linear k-ε turbulence model doi: http://dx.doi.org/10.3329/jname.v8i2.6984 Journal of Naval Architecture and Marine Engineering 8(2011) 149-163